2017
DOI: 10.4172/2161-1149.1000225
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis in Sickle-Cell Population: Pathophysiologic Insights, Clinical Evaluation and Management

Abstract: The advent of hydroxyurea and advanced medical care, including immunizations has led to improved survival among patients with Sickle Cell Disease (SCD). This prolonged survival however, introduces a chronic inflammatory disorder, Rheumatoid Arthritis (RA), which presents at a relatively older age and is rarely reported among SCD patients. In this review, we highlight the epidemiological association of SCD-RA and discuss the underlying common pathogenetic mechanisms, such as endothelial dysfunction, the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…57 L-Glutamine improves nitric oxide bioavailability and mitigates oxidative stress, which could potentially reduce the oxidative damage from RA. 56 After initiating RA therapy and SCD-directed therapy with L-glutamine, the patient reported significant improvement in RA-specific symptoms -joint pain, swelling, and stiffness, and successfully tapered his opioids to <90 MME/day within 6 months with and experienced improved bowel motility. He continues to report mild neuropathic pain symptoms that are tolerable.…”
Section: Management Decisions For Case 1: Addressing Cyclic Opioid Wimentioning
confidence: 96%
See 2 more Smart Citations
“…57 L-Glutamine improves nitric oxide bioavailability and mitigates oxidative stress, which could potentially reduce the oxidative damage from RA. 56 After initiating RA therapy and SCD-directed therapy with L-glutamine, the patient reported significant improvement in RA-specific symptoms -joint pain, swelling, and stiffness, and successfully tapered his opioids to <90 MME/day within 6 months with and experienced improved bowel motility. He continues to report mild neuropathic pain symptoms that are tolerable.…”
Section: Management Decisions For Case 1: Addressing Cyclic Opioid Wimentioning
confidence: 96%
“…In addition, the proinflammatory state and ischemic changes from VOCs can exacerbate the bone erosions and cartilage damage associated with RA. 56 OSA is often associated with nighttime hypoxia. This may trigger increased sickling and further exacerbate inflammatory pain and VOC; therefore, the underlying SCD must also be meticulously managed.…”
Section: Management Decisions For Case 1: Addressing Cyclic Opioid Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research identified that individuals of black heritage (18-85 years) sleep either too long or too little and that this is attributed to health issues such as heart disease, arthritis and depression [63]. These associations are found in SCA as well [14,64,65]. Currently, only a couple of cross-sectional studies have compared SCA to ethnicity matched controls and found individuals with SCA to have lower TST [36][37][38].…”
Section: Sleep Characteristicsmentioning
confidence: 99%
“…Treatment of RA in patients with SBT includes the use of non-NSAIDs (non-steroidal anti-inflammatory drugs) for immediate pain relief, hydroxyurea for SBT, and early addition of disease-modifying antirheumatic drugs (DMARDs) to limit disease progression. Hydroxychloroquine was prescribed to our patient due to no known deleterious interactions with hydroxyurea [ 11 ]. Blood counts, and liver and renal functions were followed in our patient, which was normal at the two-week follow-up.…”
Section: Discussionmentioning
confidence: 99%